Elevated CO2 and warming change the nutrient status and use efficiency of Panicum maximum Jacq - Carvalho, Juliana Mariano [UNESP]; Barreto, Rafael Ferreira [UNESP]; De Mello Prado, Renato [UNESP]; Habermann, Eduardo; Branco, Roberto Botelho Ferraz; Martinez, Carlos Alberto (Public Library of Science (PLoS), 2020)
Panicum maximum Jacq. 'Mombaça' (Guinea grass) is a C4 forage grass widely used in tropical pastures for cattle feeding. In this study, we evaluated the isolated and combined effects of warming and elevated CO2 concentration [CO2] during summer on nutrient content, nutrient accumulation, nutrient use efficiency and growth of P. maximum under field conditions. Field temperature and [CO2] were controlled by temperature free-air controlled enhancement and free-air CO2 enrichment systems, respectively. We tested two levels of canopy temperature: Ambient temperature (aT) and 2°C above ambient temperature (eT), as well as two levels of atmospheric [CO2]: Ambient [CO2] (aCO2) and 200 ppm above ambient CO2 (eCO2). The experiment was established in a completely randomized design with four replications, in a 2×2 factorial scheme. After pasture establishment, plants were exposed to the treatments during 30 days, with evaluations at 9, 16, 23 and 30 days after the treatments started. Results were dependent on the time of the evaluation, but in the last evaluation (beginning of the grazing), contents of N, K, Mg and S did not change as a function of treatments. However, P decreased as a function of warming under both levels of [CO2], and Ca increased under [eCO2] combined with warming. There was an increase in root dry mass under warming treatment. Combined treatment increased N, Ca and S accumulation without a corresponding increase in the use efficiency of these same nutrients, indicating that the fertiliser dose should increase in the next decades due to climate change. Our short-term results in young and well fertilized pasture suggest that under the combination of [eCO2] and eT conditions, P. maximum productivity will increase and the nutritional requirement for N, Ca and S will also increase.